Knowledge, Practice, and Associated Factors of Home-Based Management of Diarrhea among Caregivers of Children Attending Under-Five Clinic in Fagita Lekoma District, Awi Zone, Amhara Regional State, Northwest Ethiopia, 2016. (21st August 2017) - Desta, Bogale Kassahun; Assimamaw, Nega Tezera; Ashenafi, Tesfaye Demeke
Abstract : Introduction . In Ethiopia, it is the second cause for clinical presentation among under five-year child population. Objective . The main aim of this study was to assess knowledge, practice, and associated factors of home-based management of diarrhea among caregivers of children attending the under-five clinic. Methods . Institution based quantitative cross-sectional study was carried out from March 1, 2016, to April 22, 2016. Results . Two hundred eight (56.2%) of them had good knowledge and one hundred thirty-nine (37.6%) of them had the good practice of home management of diarrhea, specifically, primary education (AOR: 5.384, 95% CI: 2.008, 14.438), secondary and above education (AOR: 11.769, 95% CI: 3.527, 39.275), daily laborer (AOR: 0.208, 95% CI: 0.054, 0.810), and no information about diarrhea (AOR: 0.139, 95% CI: 0.054, 0.354). Moreover, age range of 25–35 (AOR: 4.091, 95% CI: 1.741, 9.616) and 36–45 (AOR: 3.639, 95% CI: 1.155, 11.460), being single (AOR: 0.111, 95% CI: 0.013, 0.938), being divorced (AOR: 0.120, 95% CI: 0.024, 0.598), illiteracy (AOR: 0.052, 95% CI: 0.017, 0.518), primary education (AOR: 0.143, CI: 0.046, 0.440), and no information about diarrhea (AOR: 0.197, 95% CI: 0.057, 0.685) were significantly associated variables with the outcome variables in multivariate regression. Conclusion . Caregivers had slightly adequate knowledge but poor practice.